Law Studies - G. P. Tolstopiatenko (Vestnik MGIMO-Universiteta)
At the origin of the International Law Department were such eminent scientists, diplomats and teachers as V.N. Durdenevsky, S.B. Krylov and F.I. Kozhevnikov. International law studies in USSR and Russia during the second half of the XX century was largely shaped by the lawyers of MGIMO. They had a large influence on the education in the international law in the whole USSR, and since 1990s in Russia and other CIS countries. The prominence of the research of MGIMO international lawyers was due to the close connections with the international practice, involving international negotiations in the United Nations and other international fora, diplomatic conferences and international scientific conferences. This experience is represented in the MGIMO handbooks on international law, which are still in demand. The Faculty of International Law at MGIMO consists of seven departments: Department of International Law, Department of Private International and Comparative Law; Department of European Law; Department of Comparative Constitutional Law; Department of Administrative and Financial Law; Department of Criminal Law, Department Criminal Procedure and Criminalistics. Many Russian lawyers famous at home and abroad work at the Faculty, contributing to domestic and international law studies. In 1947 the Academy of Sciences of the USSR published "International Law" textbook which was the first textbook on the subject in USSR. S.B. Krylov and V.N. Durdenevsky were the authors and editors of the textbook. First generations of MGIMO students studied international law according to this textbook. All subsequent books on international law, published in the USSR, were based on the approach to the teaching of international law, developed in the textbook by S.B. Krylov and V.N. Durdenevsky. The first textbook of international law with the stamp of MGIMO, edited by F.I. Kozhevnikov, was published in 1964. This textbook later went through five editions in 1966, 1972, 1981, 1987. In 1994 the International Law Department together with the Diplomatic Academy of the Russian Ministry of Foreign Affairs prepared new textbook, reflecting the development of international law in the 1960-1990s. In 2000 "International Law" textbook appeared, which was prepared exceptionally by the Department of International Law at MGIMO. In 2005 "European international law" textbook was published. It became the first textbook in Russian Law studies dedicated to the international legal aspects of interstate cooperation in Europe. Quarterly magazine "Moscow Journal of International Law" has made significant contribution to the development of the MGIMO international law school. Y.M. Kolosov, who is the Honored Scientist of Russia and professor of international law, was the founder of the magazine. He has been its editor in chief up to present.